Processing and microstructure of Ti-Cu binary alloys: A comprehensive review. (June 2022) - Akbarpour, Mohammad Reza; Mirabad, Homayoun Mousa; Hemmati, Amir; Kim, Hyoung Seop
Abstract: Titanium alloys are widely used in various areas, particularly in medical and dental industries, due to their remarkable properties. Still, the optimum cutting conditions for titanium alloys are under consideration. Ti alloyed with Cu has been reported to provide unique properties such as good mechanical performance, good biocompatibility, acceptable corrosion resistance, and relatively lower melting point. The properties of Ti-Cu alloys mentioned above are sensitive to microstructure. They are highly dependent on microstructural characteristics such as the formation, growth, and morphological features of intermetallics and precipitates, dependent on the amount of Cu and the manufacturing techniques employed. This study strives to scrutinize the effect of manufacturing paths on the microstructural properties of Ti-Cu alloys. To this end, prevalent fabrication procedures for Ti-Cu binary system, from casting and powder metallurgy to semi-solid metal processing and additive manufacturing, are discussed. Finally, the challenges, opportunities, merits and demerits of each technique, and future perspective are addressed.